The effect of special exercises in developing some physical abilities and achievement of the long jump under 20 years for young women - Diana Ghanim; Dr. Aseel Jaleel (الرياضة المعاصرة, 2022)
The scientific planning using of various knowledge, sciences, and modern methods in the field of kinesthetic learning, led to finding multiple exercises that correspond to the abilities of each of them and lead to the development of physical abilities and thus develop their technical performance, Therefore, the research problem identifies that the achievement of the players in the effectiveness of the long jump does not rise to the acceptable levels as a result of a weakness in the physical abilities, it has become impossible to develop these capabilities and the level of achievement in the effectiveness of the long jump, except through the learning and organized training. The researchers used the experimental method in the pre- and post-test for the experimental and control groups to suit the problem of the research. The research community was identified as 10 players in the long jump in the Specialized School for Talent Care in the 2021 sports season, as the research sample was selected by a comprehensive inventory method and the sample was divided into two groups, the experimental and control group, with (5 players) for each group. The special exercises were applied for eight weeks and for three units educational in one week, the two researchers used the statistical analysis (SPSS). The results showed a remarkable superiority between the pre- and post-test for the experimental and control groups, and the special exercises showed developing in some physical abilities and the level of achievement of the long jump for the experimental group and in favor of the post-measurement